SOSIALISASI DAN PELATIHAN PEMBUATAN YOGHURT SEBAGAI TEKNOLOGI PANGAN RUMAHAN DAN KEMANDIRIAN EKONOMI BAGI IBU RUMAH TANGGA DI PERUMAHAN DOSEN UNHAS - Hibatullah, Alnadia Yusriya; Wafaretta, Erona; Sakka, Deni Frans; Mamangkey, Jendri (Jurnal Pengabdian Masyarakat Sapangambei Manoktok Hitei, 2025)
The use of probiotics in food products, particularly yogurt, has gained increasing attention due to their prospective health benefits, such as modulating gut microbiota and enhancing immunity. A community service program was aimed to provide education and training on the production of probiotic yogurt to the women of Majelis Taklim Al-Muhajirat around Al-Muhajirin Mosque, as one of the target communities in the implemented region. The program consisted of preparation, training, and evaluation stages. The outcomes of this activity provided participants with improved knowledge, especially regarding the process of yogurt production. The program also demonstrated active participation from women with diverse backgrounds in age, education, and occupation. Based on the questionnaire results, the participants’ knowledge and skills prior to the program (pre-test) were 89%. After the program (post-test), these scores increased to 95%. This community service initiative is expected to improve the participants’ understanding of the potential for developing yogurt products within their local environment, while also creating business opportunities and additional sources of income. This activity may contribute to improving health, generating side employment, and supporting the economic well-being of families.
Keywords: probiotics; yogurt; community service